The cell-permeable iron chelator M606 inhibits MYCN-driven neuroblastoma via an E2F3-mediated response - Ruby Pandher; Chengyuan Xue; Laura D. Gamble; Giorgio Milazzo; Simone Di Giacomo; Jayne Murray; Leanna Cheung; Francesca Ferrucci; Marta Palombo; Stefania Purgato; Catherine A. Burkhart; Natalia Fedtsova; et al. (Proceedings of the National Academy of Sciences, 2025)
Despite Myc oncoproteins being major causal factors in human cancer, they remain “undruggable.” The MYCN oncogene is one of the most powerful prognostic markers for the childhood cancer neuroblastoma and represents an important target for developing novel therapeutics. Here, we report the finding and characterization of M606, a selective small molecule inhibitor of MYCN, which was identified by screening a diverse chemical library. M606 reduced MYCN protein levels in neuroblastoma cell lines and upregulated hypoxia-inducible factor 1 alpha (HIF1A). Using siRNA-mediated knockdown of MYCN , c-Myc , or HIF1A in HepG2 and BE(2)-C cells followed by M606 treatment, we demonstrated that Myc downregulation and HIF1A upregulation were two independent effects of M606 treatment. M606 selectively targeted neuroblastoma cell lines expressing higher levels of MYCN protein and delayed neuroblastoma development in the TH-MYCN transgenic mouse model. Metabolomic analysis showed that M606 modulated glucose metabolism, consistent with a hypoxic response and iron deprivation. Biochemical characterization of M606 not only confirmed its iron-chelating properties but also revealed its ability to downregulate MYCN promoter activity, which could be rescued by the addition of iron. Luciferase assays identified the minimal MYCN promoter region required for the M606 response, which contained overlapping E2F transcription factor binding sites. Further evaluation defined a key role for E2F3 in the M606-mediated response. The finding of a potent cell-permeable iron chelator that can chelate iron to directly downregulate MYCN transcription via an E2F3-mediated response represents a potentially valuable therapeutic approach in the treatment of cancers overexpressing Myc oncoproteins.